2011
DOI: 10.1098/rspb.2011.1611
|View full text |Cite
|
Sign up to set email alerts
|

Semiochemical compounds of preen secretion reflect genetic make-up in a seabird species

Abstract: Several vertebrates choose their mate according to genetic heterozygosity and relatedness, and use odour cues to assess their conspecifics' genetic make-up. In birds, although several species (including the blacklegged kittiwake) exhibit non-random mating according to genetic traits, the cues used to assess genetic characteristics remain unknown. The importance of olfaction in birds' social behaviour is gaining attention among researchers, and it has been suggested that, as in other vertebrates, bird body scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 84 publications
1
55
0
Order By: Relevance
“…The only study of a free-ranging, natural population to have detected an association with genotype used PCA to reduce the dimensionality of the chemical data (9). However, this approach is not ideally suited to detecting such signals because a principal component that explains maximal variance may not necessarily provide an optimal representation of the underlying genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only study of a free-ranging, natural population to have detected an association with genotype used PCA to reduce the dimensionality of the chemical data (9). However, this approach is not ideally suited to detecting such signals because a principal component that explains maximal variance may not necessarily provide an optimal representation of the underlying genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that females of several species are capable of discriminating potential partners based on olfactory cues (3)(4)(5). However, very few studies have demonstrated a convincing link between the molecular composition of chemical fingerprints and genetic traits, such as heterozygosity (a measure of genetic quality) and relatedness (6)(7)(8)(9). These studies were almost exclusively conducted on a captive population of lemurs, a species known for its conspicuous use of scent marking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Torres et al 2011), sociochemical compounds (e.g. Leclaire et al 2012), sex-specific foraging behaviour (e.g. Weimerskirch et al 2006), disease transmission (e.g.…”
Section: Ecologymentioning
confidence: 99%
“…In birds, individual odors are thought to originate mainly from preen gland secretions (Mardon et al, 2011) that are spread onto the plumage during preening. These secretions encode information on bird species, identity, sex and kinship (Leclaire et al, 2012;Mardon et al, 2010;Whittaker et al, 2010), and can be transferred from the parent to the egg through passive or active spreading (Martín-Vivaldi et al, 2014). Because in several avian species individuals assess preen oil odor to discriminate between conspecifics (Amo et al, 2012a;Coffin et al, 2011;Whittaker et al, 2011), they could also be able to discriminate their own eggs from other eggs using olfactory cues.…”
Section: Introductionmentioning
confidence: 99%